Estimasi Penghematan Biaya dan Perancangan Standrisasi Kerja pada Produksi Air Cleaner di PT. Astra Otoparts Divisi Adiwira Plastik - Saryadi, Richard Dwinata; Octavia, Tanti (Jurnal Titra, 2015)
The increasing of the air cleanerâs production cost was one of the problems experienced by PT. Astra Otoparts Adiwira Plastics Division. The production costs consist of three types of the cost, namely cost of materials, labor costs, and factory overhead cost. The increasing of production cost is caused by the large number of manpower who works on the production of assy air cleaner area, the use of the area, and electricity consumption. The large number of manpower affects the increasing of labor costs and the use of the area and electricity consumption affect an increase in factory overhead cost. Cost of raw materials being on the outside control of the company as the costs would come from supplier. The saving cost is calculated after improving and applying direct assy. The estimating of saving cost is Rp. 203,933,267.59 monthly. After implementing the direct assy, the work standardization is designed. The design of standardization work already performed the three types of standardizations. Those are standardized work chart (SWC), standardized work combination table (SWCT), and work instruction (WI).